Development, tryout and evaluation of instructional materials on selected mathematical topics in the computer - Aytona, Anita Javier
This study looked into the possibility of using computers to enhance the teaching and learning of selected topics in mathematics. The researcher developed, implemented and evaluated instructional materials on selected mathematical topics to be incorporated in the computer course. Thus, through this paper, a resource material is provided for all those who wish to integrate computer technology into their mathematics teaching.